Effects of platelet-rich plasma on mesenchymal stem cells isolated from rat uterus - Vishnyakova,Polina; Artemova,Daria; Elchaninov,Andrey; Efendieva,Zulfiia; Apolikhina,Inna; Sukhikh,Gennady; Fatkhudinov,Timur (PeerJ, 2020)
Background Platelet-rich plasma (PRP), which represents a valuable source of growth factors, is increasingly being applied in regenerative medicine. Recent findings suggest the feasibility of using PRP in the treatment of infertility secondary to refractory thin endometrium. Mesenchymal stem/stromal cells (MSCs) of the endometrium are an essential cellular component responsible for extracellular matrix remodeling, angiogenesis, cell-to-cell communication, and postmenstrual tissue repair. Using a rat model, we examine the effects of autologous PRP on MSCs isolated from the uterus and compare them with the effects of autologous ordinary plasma (OP) and complete growth medium. Methods MSCs were isolated from uterine tissues via enzymatic disaggregation. Flow cytometry immunophenotyping of the primary cell cultures was complemented by immunocytochemistry for Ki-67 and vimentin. The ability of MSCs to differentiate in osteo-, chondro-, and adipogenic directions was assessed using differentiation-inducing media. The levels of autophagy and apoptosis markers, as well as the levels of matrix metalloproteinase 9 (MMP9) and estrogen receptor α, were assessed by western blotting. Results After 24 h incubation, the proliferation index of the PRP-treated MSC cultures was significantly higher than that of the MSC cultures treated with complete growth medium. PRP treatment elevated production of LC3B protein, an autophagy marker, while OP treatment upregulated the expression of stress-induced protein p53 and extracellular enzyme MMP9. The results indicate practical relevance and validity for PRP use in the treatment of infertility.
Keywords: Mesenchymal stem cells; Platelet-rich plasma; Rat uterine; Plasma; Endometrium